1952
DOI: 10.1149/1.2779652
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Zinc Corrosion Products

Abstract: An investigation was made, using x-ray diffraction methods, of the nature of the corrosion products formed on zinc when immersed in hot or cold water, and of the changes occurring when zinc hydroxide and zinc oxide were kept hot or cold in air or under water. Complicated results were obtained, but it is clear that zinc oxide may be a product of the corrosion of zinc in water, especially at elevated temperatures. The significance of the results is discussed in the light of previous work on the electrochemical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
5

Year Published

1955
1955
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 2 publications
0
10
0
5
Order By: Relevance
“…Formation of hydroxyl on the zinc surface is under a mixed control of diffusion/activation and an increase in the temperature appears to prolong the hydroxyl formation time [20]. Kotnik [21] and Gilbert [22] reported that zinc hydroxyl is usually produced in cold water (0-30 • C) whereas in hot water (30-90 • C) the surface product is mainly zinc oxide. On the other hand, when the sample treated in hot water is exposed to the ambient air, water molecules are expected to be adsorbed from the air [23].…”
Section: Surface Oxide Compositionmentioning
confidence: 99%
“…Formation of hydroxyl on the zinc surface is under a mixed control of diffusion/activation and an increase in the temperature appears to prolong the hydroxyl formation time [20]. Kotnik [21] and Gilbert [22] reported that zinc hydroxyl is usually produced in cold water (0-30 • C) whereas in hot water (30-90 • C) the surface product is mainly zinc oxide. On the other hand, when the sample treated in hot water is exposed to the ambient air, water molecules are expected to be adsorbed from the air [23].…”
Section: Surface Oxide Compositionmentioning
confidence: 99%
“…Aufnahmen von StromdichtePotentiaI-Kurven von Eisen bzw. Stahl in Nitratlosungen konnten u. a. zeigen, da8 sich das den Korngrenzenangriff kennzeichnende Grenzpotential unter dem EinfluB von Zugspannungen zu negativen Werten und damit zum Ruhepotential hin verschiebt (8,9).…”
Section: Grundlagenunclassified
“…Zen ist zunachst das Vorhandensein von Passivschichten an den korngrenzenfreien Bereichen der Stahloberflache und den durch einen interkristallinen Angriff freigelegten Kornflachen (3,8,(10)(11)(12)(13)(14)(15) (2,8,9,23,(25)(26)(27)(28). Der wesentliche EinfluD des Kohlenstoffes erfolgt uber die beobachtete Bildung eines gleichmafiigen Zementitsaumes auf den Kornflachen (9,23,29 (3,9).…”
Section: Grundlagenunclassified
“…Wirtz, Dusseldorf) elektropoliert, wobei Temperatur, Zeitdauer und Zusammensetzung des Polierelektrolyten mai3gebend waren (3): Am besten hat sich der Elektrolyt 144 ml Athanol, 32 ml H,O, 10 g AICl,, 16 ml Butanol, 45 g ZnC1, bei 35-40 V, 0,2 A, 1,5 bis 2 min bei 10 Die Auszahlung der Lochfraflstellen und die Abschatzung der Flachenkorrosion wurde sowohl mittels (SE)-Aufnahmen bei etwa 20-facher Vergroflerung als auch lichtoptisch vorgenommen. Von den von Feitknedt und Mitarbeitern beschriebenen Modifikationen von Znkhydroxyd konnte rontgenografisch unter naturlichen Korrosionsverhaltnissen keine Modifikation eindeutig nachgewiesen werden (2), so dai3 eine rasterelektronenmikroskopische Untersuchung der Heii3wasserkorrosion des Zinks von besonderem Interesse war.…”
unclassified
“…SE, 20 OC,10 min, 50 X Pit, Aurbildungsform na& Evans Bei 40 OC erfolgt der narbenformige Angriff wesentlich rascher; schon nach 5 min sind die Pits gut entwickelt und haben einen ausgepragten Randwall. SE, 20 OC, 80 min, 2000 X Detail eines Pit-Ringes Abb 3…”
unclassified